National Geographic fashion / by Cathy Newman ; introductions by Joanne B. Eicher and Valerie Mendes. - Newman, Cathy. (National Geographic, 2001)
Fashion explores clothing and adornment from a uniquely global perspective, at a time when current fashion is fusing diverse cultural styles as never before. Essays, drawn from interviews with prominent fashion industry insiders-including contemporary designers, fashion editors, and curators-give new insights into the role fashion has played in history, while Newman's essays focus on the body adorned, from hair to garb accessories. The book's introductory essays are written by cultural anthropologist Joanne Eicher and fashion historian Valerie Mendes.